Hazards of Short- and Long-term Administration of Glucocorticoids on the Periodontium in Rats: A Histological and Electron Microscopic Study - Hagag, Tahani Abd El Karim; Fathy, Elham; Mahmoud, Mahmoud Fathy; salem, zeinab (Journal of Dentistry Indonesia, 2019)
The administration of glucocorticoids is proven to cause serious adverse events. Objectives: This study was conducted to compare the possible hazards of the short- and long-term administration of glucocorticoids on the periodontium in rats, using histological examination and scanning electron microscopy. Methods: Fifteen adult male albino rats were included in the study and divided into the 3 groups. Group I served as a control, group II received 7 mg/kg dexamethasone intramuscularly once a week for 5 wk, and group III received 7 mg/kg dexamethasone intramuscularly once a week for 10 wk. The mandibles were dissected and examined histologically as well as with scanning electron microscopy and energy dispersive radiography. Results: Histologically, group I showed normal an alveolar process. In group II, bone trabeculae demonstrated obvious Howship’s lacunae of osteoclasts. In group III, bone trabeculae exhibited multiple degenerated osteocytes with apparent vacuolization. Scanning electron microscopy revealed smooth alveolar bone architecture in group I. Groups II and III demonstrated irregular bone architecture with widening of the neurovascular canals. EDX analysis demonstrated the highest calcium-phosphorous concentration in the control group and the lowest in group III. Conclusions: Dexamethasone has a devastating impact on the alveolar bone via the acceleration of bone resorption and decreased activity of osteoblasts. This effect was more pronounced with prolonged drug administration.